Navigating “Tanah Musnah”: Governance Dilemmas and Social Impacts in the Semarang-Demak Toll Road Land Acquisition - Westi Utami; Tri Idawijayanti; Lutfia Nursetya Fuadina; Reza Nur Amrin (Sekolah Tinggi Pertanahan Nasional, 2026)
The Semarang-Demak Toll Road National Strategic Project (PSN) is a solution to boost the economy, alleviate congestion, and adapt to climate change. The long-term construction of the Semarang-Demak toll road (2019–2023) has been hampered by land acquisition on the route inundated by tidal flooding. This study aims to analyze the problems and policies of land acquisition in cases of lost land. The research was conducted using a descriptive qualitative approach to examine the problems, policies, and governance issues of land acquisition in three villages (Bedono, Sriwulan, and Purwosari). The findings demonstrate that land subsidence and climate-induced tidal flooding caused the physical disappearance of land parcels, rendering standard statutory mechanisms inapplicable. Therefore, the government introduced a compassionate compensation scheme under Presidential Regulation No. 27 of 2023 to mitigate the social impacts experienced by affected communities, as the assessment of this lost land has implications for the incapacity to provide compensation. This scheme is referred to as a compassionate fund (dana kerohiman). Although the scheme cannot fully compensate for the communities' economic and social losses, but on the other hand, this mechanism is a solution for handling social impacts on the community.